Praziquantel-encapsulated niosomes against Schistosoma mansoni with reduced sensitivity to praziquantel - Eglal I. Amer; Iman Fathy Abou-El-Naga; Laila M. Boulos; Heba S. Ramadan; Salwa S. Younis (Biomédica, 2022)
Introduction: Praziquantel (PZQ) is the only commercially available drug for schistosomiasis. The current shortage of alternative effective drugs and the lack of successful preventive measures enhance its value. The increase in the prevalence of PZQ resistance under sustained drug pressure is, therefore, an upcoming issue. Objective: To overcome the tolerance to PZQ using nanotechnology after laboratory induction of a Schistosoma mansoni isolate with reduced sensitivity to the drug during the intramolluscan phase. Materials and methods: Shedding snails were treated with PZQ doses of 200 mg/kg twice/ week followed by an interval of one week and then repeated twice in the same manner. The success of inducing reduced sensitivity was confirmed in vitro via the reduction of cercarial response to PZQ regarding their swimming activity and death percentage at different examination times. Results: Oral treatment with a single PZQ dose of 500 mg/kg in mice infected with cercariae with reduced sensitivity to PZQ revealed a non-significant reduction (35.1%) of total worm burden compared to non-treated control mice. Orally inoculated PZQ-encapsulated niosomes against S. mansoni with reduced sensitivity to PZQ successfully regained the pathogen’s sensitivity to PZQ as evidenced by measuring different parameters in comparison to the non-treated infected animals with parasites with reduced sensitivity to PZQ. The mean total worm load was 1.33 ± 0.52 with a statistically significant reduction of 94.09% and complete eradication of male worms. We obtained a remarkable increase in the percentage reduction of tissue egg counts in the liver and intestine (97.68% and 98.56%, respectively) associated with a massive increase in dead eggs and the complete absence of immature stages. Conclusion: PZQ-encapsulated niosomes restored the drug sensitivity against laboratory-induced S. mansoni adult worms with reduced sensitivity to PZQ.